Effects of a combination of niacin and chromium (III)-chloride on the skin and lungs of hyperlipemic rats - Yanardag, R; Peksel, A; Yesilyaprak, B; Doger, MM; Arisan-Atac, I (SPRINGERNATURE, 2005)
The aim of this study was to investigate the biochemical effects of niacin and chromium(III)-chloride on serum lipid peroxidation, uric and sialic acids, and the extent of lipid peroxidation and glutathione levels in skin and lung tissues of hyperlipidemic rats. In this study, female Swiss albino rats, 12 mo old, were used. They were randomly divided into four groups. Group I animals were fed with a standard pellet diet and water ad libitium. Group 11 rats were fed with a standard pellet diet and were treated with a dose of 250 mu g/kg body weight CrCI3 center dot 6H(2)O and 100 rng/kg body weight niacin, for 45 d, by the gavage technique. Group III rats were fed a lipogenic diet in which 2% cholesterol, 0.5% cholic acid, and 20% sunflower oil were added to the pellet chow. In addition, the animals in this group drank water containing 3% ethanol. This regime was maintained for 60 d. The rats in group IV were maintained in the same food and drink regime as the animals in group III. After 2 wk, the animals showed symptoms of hyperlipemia and they were treated with 250 mu g/kg body weight CrCI(3 center dot)6H(2)O and 100 mg/kg body weight niacin, by gavage, for 45 d. On d 60, the blood and the skin and lungs samples were taken from animals. In the hyperlipemic groups, a reduction of the lung glutathione level and an increase in serum, lung, and skin lipid peroxidation levels and in serum sialic and uric acid were observed. In rats treated with a combination of niacin and Cr(III), the skin and serum lipid peroxidation and the sialic and uric acid levels decreased while showing an increase of lung glutathione activity. These results suggest that niacin and Cr(III), when administered in combination, have a protective effect against skin and lung tissues damage as a result of hyperlipidemia.
Keywords: hyperlipemia; skin; lungs; glutathione; lipid peroxidation; niacin; chromium; sialic acid; uric acid; TYPE-2 DIABETES-MELLITUS; LIPID-PEROXIDATION; SIALIC-ACID; CARDIOVASCULAR-DISEASE; OXIDATIVE STRESS; SERUM-CHOLESTEROL; HYPERCHOLESTEROLEMIA; DEFICIENT; SUPPLEMENTATION; ANTIOXIDANTS; Biochemistry & Molecular Biology; Endocrinology & Metabolism